X(x-3)=x+3

Simple and best practice solution for X(x-3)=x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X(x-3)=x+3 equation:


Simplifying
X(x + -3) = x + 3

Reorder the terms:
X(-3 + x) = x + 3
(-3 * X + x * X) = x + 3
(-3X + xX) = x + 3

Reorder the terms:
-3X + xX = 3 + x

Solving
-3X + xX = 3 + x

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Reorder the terms:
-3 + -3X + -1x + xX = 3 + x + -3 + -1x

Reorder the terms:
-3 + -3X + -1x + xX = 3 + -3 + x + -1x

Combine like terms: 3 + -3 = 0
-3 + -3X + -1x + xX = 0 + x + -1x
-3 + -3X + -1x + xX = x + -1x

Combine like terms: x + -1x = 0
-3 + -3X + -1x + xX = 0

The solution to this equation could not be determined.

See similar equations:

| 9+6k-8k^2=0 | | 5+7x-6x^2=0 | | 2x^2+7x+14=0 | | 6a^2-5a-2=0 | | 2x^2+7+14=0 | | 6a^2-51-2=0 | | r^2-8r=0 | | 4y^2-y-3=0 | | (2x^3*-7)(6x^3-6)=0 | | 8m^3n^4-22m^5n^6= | | -7x^2-66x-27=0 | | (x-5)(x+1)=4 | | 2+5*x=4x | | 3r^2-2r-5=0 | | -6y-5=7+9y | | 3r^2-24-5=0 | | 10r+8=58 | | 72m^7n+24n= | | 49m^5n^3+28mn^4= | | a^2+13a-68=0 | | 10m^3n^2-25m^2n^3= | | 2s+9s+20=128 | | 7p+9=8p+4 | | 3(x-2)=-2x-16 | | m^3n+9m^2n= | | 4(2x+3u)-3(x-y)= | | 9x^3+30x= | | 45x^2-20x= | | 2*N=12 | | 2XN=12 | | 29-(2c+3)=2(c+3)+c | | p^2+2pq+q^2-2p-2q-15=0 |

Equations solver categories